2017
DOI: 10.1016/j.cmi.2016.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Week 4 response predicts sustained virological response to all-oral direct-acting antiviral-based therapy in cirrhotic patients with hepatitis C virus genotype 3 infection

Abstract: TW4-response indicates the probability of achieving SVR to currently used DAA-based therapy in HCV genotype 3-infected individuals with cirrhosis. This finding may be useful to tailor treatment strategy in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
(13 reference statements)
0
4
0
1
Order By: Relevance
“…But it signifies nothing more than the fact that the observed sample is too small to detect a population effect [63]. Hepatitis C patients can achieve SVR12 at week 4 of treatment with the oral DAA-based therapy [64]. BLC has shown a decline in the HCV-RNA after 12 weeks of treatment in hepatitis C patients [48].…”
Section: Discussionmentioning
confidence: 99%
“…But it signifies nothing more than the fact that the observed sample is too small to detect a population effect [63]. Hepatitis C patients can achieve SVR12 at week 4 of treatment with the oral DAA-based therapy [64]. BLC has shown a decline in the HCV-RNA after 12 weeks of treatment in hepatitis C patients [48].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SVR12 rates were not impacted by time to first undetectable HCV RNA . In contrast, a recent Spanish multicohort study suggested that the response at treatment week 4 is predictive of SVR in HCV genotype 3‐infected patients. The population of this study was however different from that in our study, as patients were receiving different DAA combinations with ribavirin (SOF+DCV+RBV; SOF/LDV+RBV or SOF+RBV).…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Additional evidence has suggested that viral response at week 4 is still predictive of SVR12 with interferon-free DAA regimens, particularly in more difficult-to-treat populations such as genotype 3 patients with cirrhosis. [21][22][23] A study of 21,095 veterans on interferon-free regimens showed a significant association between detectable week 4 HCV RNA and lower SVR rates, which decreased with increasing baseline viral load. 24 The American Association for the Study of Liver Diseases and Infectious Diseases Society of America (AASLD-IDSA) hepatitis C guidance recommends measuring HCV RNA at week 4 of treatment for all patients on DAA therapy.…”
mentioning
confidence: 99%